2019
DOI: 10.35940/ijrte.b1510.078219
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and Agriculture 5. 0

Abstract: Abstract : Use of Artificial Intelligence and Robotics in agriculture is called as Agriculture 5.0 Disruptive technology should help in solving the social needs . Rogers suggest to develop human centric " Ubiquitous Computing " solution , for specific domain (agriculture production). Crop yield prediction (CYP) is vital to address the ever growing demand of food requirements of burgeoning world population and to prevent starvation . Artificial Intelligence can offer effective and practical solution for the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Notably, the employment of robotic chefs to predict and ameliorate food quality as showcased by Zhu and Chang (2020) testify that AI holds a transformative power. Future studies could focus on deepening the knowledge of AI-driven technologies' role in business ecosystems (Yang et al, 2020), and understanding how machine learning could improve yield prediction (Murugesan et al, 2019).…”
Section: Discussion: An Interpretive Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the employment of robotic chefs to predict and ameliorate food quality as showcased by Zhu and Chang (2020) testify that AI holds a transformative power. Future studies could focus on deepening the knowledge of AI-driven technologies' role in business ecosystems (Yang et al, 2020), and understanding how machine learning could improve yield prediction (Murugesan et al, 2019).…”
Section: Discussion: An Interpretive Frameworkmentioning
confidence: 99%
“…Future studies could focus on deepening the knowledge of AI-driven technologies' role in business ecosystems (Yang et al. , 2020), and understanding how machine learning could improve yield prediction (Murugesan et al. , 2019).…”
Section: Discussion: An Interpretive Frameworkmentioning
confidence: 99%
“…The correlation be-tween Farming 4.0 and the 4.0 industrial revolution, regarding the improvement of the mechanization of fieldwork, is observed in [39]. Experts in the field of Farming 5.0 and food security have found that the use of artificial intelligence, robotics, machine learning (ML), and deep learning (DL) can predict crop yields with a 75% probability, detect agricultural diseases that affect crop quality, and increase the profitability of farms [40]. In crop production, the transition from smart farming to the agricultural revolution 5.0 should be associated with more significant gain in yield, sustainability, and environmental conservation [41].…”
Section: Agricultural Revolutionmentioning
confidence: 99%
“…The use of sequential Gaussian Simulation for modelling water table spatial variables has been investigated and also measure the risk present in the shallow water tables is calculated as 95% [14]. Murugesan et al [15] demonstrate that crop prediction models may be achieved using ML with an accuracy of up to 75%. This paper achieved 100% prediction of crop production with 14 micronutrient soil features which can be used by expert advisory to harvesting stage from seed stage.…”
Section: Literature Reviewmentioning
confidence: 99%